Brachial Artery Aneurysm as a Limb Threatening Condition: a Case Report - Heydari, Farhad; Esmailian, Mehrdad; Taheri, Mehrsa (Archives of Academic Emergency Medicine, 2018)
Brachial artery aneurysms are rare but potentially limb threatening condition. The presented case here is a 52-year old male referred to the emergency department complaining a sudden onset and progressive pain with coldness of his right upper extremity during brushing. The right upper extremity was pulseless and three-dimensional computed tomography showed an aneurysm of the proximal right brachial artery associated with arterial occlusion in its distal branch. Embolectomy was done, the aneurysm resected, and the artery successfully re-vascularised by interposing a saphenous vein graft.